Bone Mineral Density Assessment in Ankylosing Spondylitis and Characteristics of Bone Turnover Parameters - Füsun Şahin; Nurdan Kotevoğlu; Banu Kuran (Türk Osteoporoz Dergisi, 2005)
Ankylosing spondylitis, characterised with excessive new bone formation and calcification in spine and peripheral joints, causes osteoporosis which is a general component of inflammatory arthritis. Since is excessive bone formation affects bone mineral density, there are problems in diagnosis and follow-up of osteoporosis efforts made for finding the right diagnostic tool. Besides bone metabolism and turn-over in inflammatory diseases should be known in detail, because it has a place in diagnosis and follow-up. In this review, bone mineral density in ankylosing spondylitis, the importance and usage of bone turn-over parameters are discussed in the light of literature data.